The Convention on the Rights of Persons with Disabilities and the Labor Rights of Persons with Disabilities in Peru - Ato Alvaro, Martin Eduardo (2024)
In this study, an exhaustive analysis of the labor rights of individuals with disabilities will be carried out, as well as their regulation in the 2006 Convention on the Rights of Persons with Disabilities, as well as in national regulations and jurisprudence. The right to access and continuity in employment for this group will be explored, examining the criteria that both government entities and private companies must follow to avoid any form of discrimination. In addition, various court cases will be examined, both nationally and internationally, involving the labor rights of people with disabilities. It will be concluded that disability discrimination is a deep-rooted problem in Peruvian society, which has been adequately addressed in the field of constitutional and national supreme justice, recognizing and supporting respect for the labor rights of this population group.